2005
DOI: 10.1055/s-2004-830062
|View full text |Cite
|
Sign up to set email alerts
|

Aktuelle Rückfalldaten der Essener prospektiven Prognosestudie

Abstract: The prediction of dangerousness in mentally disordered offenders -- and here mainly the issue of safety -- is still of primary interest for forensic experts and the public. The effectiveness of treatment and therefore of the whole German forensic system is generally measured by recidivism rates of this clientele. This article presents topical recidivism rates of 255 mentally ill offenders after a minimum time at risk of 2 years (mean 4 years). Data are collected in the Essener prospective multicenter study fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
1
0
8
Order By: Relevance
“…International studies on (medium security) forensic psychiatric treatment have presented a mixed picture of recidivism rates that seems to vary from 7.1% to 63% for general recidivism and from 1.8% to 46% for violent recidivism over different follow-up periods of 1 to 10.8 years in NGRI populations (for an overview, see Hayes, Kemp, Large, & Nielssen, 2014) (studies not reported in Hayes et al, 2014;Edwards, Steed, & Murray, 2002;Friendship, McClintock, Rutter, & Maden, 1999;Harris, Rice, & Cormier, 2002;Lund, Hofvander, Forsman, Anckarsater, & Nilsson, 2013;Maden, Scott, Burnett, Lewis, & Skapinakis, 2004;Müller-Isberner, Freese, Jockel, & Gonzalez Cabeza, 2000;Nilsson, Wallinius, Gustavson, Anckarsäter, & Kerekes, 2011;Nowak & Nugter, 2014;Seifert & Moller-Mussavi, 2005;Tabita, de Santi, & Kjellin, 2012). To the best of our knowledge, no meta-analysis of recidivism rates in NGRI patients is currently available.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 99%
“…International studies on (medium security) forensic psychiatric treatment have presented a mixed picture of recidivism rates that seems to vary from 7.1% to 63% for general recidivism and from 1.8% to 46% for violent recidivism over different follow-up periods of 1 to 10.8 years in NGRI populations (for an overview, see Hayes, Kemp, Large, & Nielssen, 2014) (studies not reported in Hayes et al, 2014;Edwards, Steed, & Murray, 2002;Friendship, McClintock, Rutter, & Maden, 1999;Harris, Rice, & Cormier, 2002;Lund, Hofvander, Forsman, Anckarsater, & Nilsson, 2013;Maden, Scott, Burnett, Lewis, & Skapinakis, 2004;Müller-Isberner, Freese, Jockel, & Gonzalez Cabeza, 2000;Nilsson, Wallinius, Gustavson, Anckarsäter, & Kerekes, 2011;Nowak & Nugter, 2014;Seifert & Moller-Mussavi, 2005;Tabita, de Santi, & Kjellin, 2012). To the best of our knowledge, no meta-analysis of recidivism rates in NGRI patients is currently available.…”
Section: Medium Security Treatment and Recidivism Ratesmentioning
confidence: 99%
“…Den Erfolg der Unterbringung im Maßregelvollzug an den Krite− rien der Aussetzung zur Bewährung bzw. der Legalbewährung zu messen, ist durch die kaum von einem Studiendesign erfass− bare Individualität der Verurteilten und das Fehlen von Ver− gleichsgruppen kritisch zu betrachten [9,14]. Zumindest haben sich diese Merkmale aber als Indikatoren einer erfolgreichen Be− handlung in einer Entziehungsanstalt, insbesondere in Erman− gelung weiterer relativ gut zugänglicher und messbarer Erfolgs− kriterien, und als Vergleichsgröße etabliert [5,12,14].…”
unclassified
“…Abb. Die schlechten sozialen Start− und Rahmenbedingungen bei Maßregelvollzugspatienten sind bereits wiederholt thematisiert worden [5,6,8,14]. In der eigenen Studie war mehr als ein Drittel der Patienten ohne jeglichen beruflichen Abschluss.…”
unclassified
“…Die Daten stammen aus der DFG−finanzierten Essener prospekti− ven Prognosestudie (zur Methodik [13], zum Gesamtüberblick [14]), an der 23 …”
Section: Methodeunclassified